Outcomes of isolated surgical aortic valve replacement in the era of transcatheter aortic valve implantation. Issue 7 (3rd May 2020) - Ram, Eilon; Amunts, Sergei; Zuroff, Elchanan; Peled, Yael; Kogan, Alexander; Raanani, Ehud; Sternik, Leonid
Abstract: Background and Aims: Until early into the 21st century, the only therapeutic option for aortic valve (AV) stenosis was surgical aortic valve replacement (AVR), but this changed with the introduction of transcatheter aortic valve implantation (TAVI). Our objective was to present the results of surgical AVR performed in low‐risk patients in the era of TAVI, in a large tertiary medical center. Methods: Data from low surgical risk patients (defined as Euroscore < 5) greater than 60 years of age, who underwent isolated AVR surgery between 2004 and 2018, were obtained from our departmental database. Of the 313 study patients, 110 (35%) underwent isolated AVR before 2010 (early period) and 203 patients (65%) underwent the same procedure from 2010 onward (late period). Results: Mean age was 67 ± 5 years and 182 (58%) were male. Fifty‐six patients (18%) had a unicuspid or bicuspid AV. Patient characteristics were similar between the early and late periods. There was no in‐hospital or 30‐day mortality throughout the entire cohort, with one case (0.3%) of postoperative stroke. Permanent pacemaker implantation was required in 2.2% (N = 7). Patients in the early period required significantly more re‐exploration due to bleeding/tamponade (8.2% vs 1.5%; P = .008). Long‐term mortality (1, 3, and 5 years) was higher in the early compared with the late period (2.7% vs 1%, 7.3% vs 3%, and 15.5% vs 3.4%, respectively; log‐rank P = .005). Conclusions: Surgical AVR provides excellent short‐ and long‐term results with low morbidity and mortality in low surgical risk patients. While patient characteristics did not change dramatically over the years, the long‐term results were encouraging.